8 - The Concept of Innovation and the South African Nation - Osha, sanya (Africa Development, 2021)
This article follows the birth of the South African nation and how it intersects with the emergence of evolutionary economics as a major academic paradigm. It also recounts virtually all the significant historical phases of South African politics, ideological configuration and industrial development up to the emergence of the knowledge economy. Some of these phases include the se regationist period, the apartheid regime and the current democratic era.